2020
DOI: 10.1051/e3sconf/202014103007
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Profiles, Antioxidant and Antibacterial Capacity of Honey from Stingless Bee Tetragonula laeviceps Species Complex

Abstract: Stingless bee (Apidae, Meliponini) is a group of eusocial insects that widely distributed in the neotrophic regions of the globe. Similar to honeybees, stingless bees produce honey that is usually valued much higher, likely due to both its unique flavor and properties. In this study, honey samples produced by stingless bee Tetragonula laeviceps species complex were collected from different meliponary in Eastern Thailand (Rayong, Chantaburi, and Trat provinces). The honey samples were examined the physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
(37 reference statements)
1
10
0
1
Order By: Relevance
“…In addition, the acidity also gives extra flavour to the honey and is an indicator of microbial stability, as most bacteria cannot grow in an acidic environment [17]. Several reports that comply with the Malaysian Standards are from the species of Tetragonula fuscobalteata (Cameron, 1908), Tetragonula laeviceps-pagdeni complex, Tetragonula testaceitarsis (Cameron, 1901), Tetrigona melanoleuca (Cockerell, 1929), Tetrigona apicalis (Smith, 1857) [11], Tetragonula laeviceps [18], and Tetrigona binghami (Schwarz, 1937) [19,20].…”
Section: Stingless Bee Honeymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the acidity also gives extra flavour to the honey and is an indicator of microbial stability, as most bacteria cannot grow in an acidic environment [17]. Several reports that comply with the Malaysian Standards are from the species of Tetragonula fuscobalteata (Cameron, 1908), Tetragonula laeviceps-pagdeni complex, Tetragonula testaceitarsis (Cameron, 1901), Tetrigona melanoleuca (Cockerell, 1929), Tetrigona apicalis (Smith, 1857) [11], Tetragonula laeviceps [18], and Tetrigona binghami (Schwarz, 1937) [19,20].…”
Section: Stingless Bee Honeymentioning
confidence: 99%
“…It has been proven that stingless bee honey has the potential to inhibit bacteria [8,18,25,30,[53][54][55][56][57][58]. Researchers Hasali et al [58] stated that honey produced by Heterotrigona itama showed greater inhibition of P. aeruginosa compared to commercial antibiotics, indicating better antibacterial activity against pathogenic bacteria.…”
Section: Antimicrobialmentioning
confidence: 99%
“…The high antibiotic content present in the honey of stingless bees may be one of the reasons why rapid fermentation is avoided, as long as contaminations during collection are kept to a minimum. Laboratory tests of stingless bee honey have, for example, revealed that stingless bee honey is a more powerful inhibitor of bacteria than honey from A. mellifera bees < 7 < 7 < 7 < 7 <.7 Lactose (g/100 g honey) < 7 < 7 < 7 < 7 < 7 Maltose (g/100 g honey) < 7 < 7 < 7 < 7 < 7 Coliforms MPN < 3 < 3 < 3 < 3 < 3 Organisms of fecal origin < 3 < 3 < 3 < 3 < 3 (BRADBEAR, 2009;RODRÍGUEZ-MALAVER et al, 2009;YAACOB, et al, 2017;AMIN et al, 2018;KHONGKWANMUEANG et al, 2020).…”
Section: Physicochemical and Microbiological Characterization Of Honeymentioning
confidence: 99%
“…Honey from multiple species of stingless bee exhibit a great potential for human consumption and commercialization due to the higher content of polyphenolic compounds, flavonoids, and antioxidants, as compared with Apis mellifera honey (RODRÍGUEZ-MALAVER et al, 2009;OLIVEIRA et al, 2012;KHONGKWANMUEANG et al, 2020). In addition, bioactive, therapeutic, and medicinal effects of stingless bee honeys have been documented across different stingless bee species (WATANABE et al, 2014;BILUCA et al, 2016;RAO et al, 2016;YAACOB et al, 2017;AMIN et al, 2018;KHONGKWANMUEANG et al, 2020). Globally, there are more than 500 species of stingless bees, the majority of which are described from the Neotropical and Sub-Tropical region (CAMARGO & PEDRO, 2007;MICHENER, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to honey from Apis mellifera, the honey produced by stingless bees has several sensory particularities, like less sweetness, more acidic flavor and more fluid texture, as well as some different physicochemical properties, especially in sugars composition and amount, moisture and acidity (Nordin et al, 2018). Studies show that honey from stingless bees, in addition to having different nutritional properties, has therapeutic applications with promising results, with the presence of antioxidant capacity bioactive compounds (Ávila et al, 2018a;Biluca et al, 2016;Ooi et al, 2021), potential to antimicrobial (Khongkwanmueang et al, 2020) and antiproliferative cell activities (Ismail et al, 2018).…”
Section: Introductionmentioning
confidence: 99%